Analysis of Frequency and Risk Factors Associated with Discitis Followed by Disc Surgeries for Prolapsed Inter-Vertebral Disc - Adnan Munir; Muhammad Idris Khan; Laiba Fasihat; Sadiq Ur Rehman (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Postoperative discitis, an inflammatory and infectious complication, can arise following disc surgeries for PIVD (Prolapsed Intervertebral Disc). Aim: To comprehensively examine patient demographics, affected spinal regions, surgical interventions, and risk factors related to postop discitis, providing vital insights for enhanced management and preventive measures with respect to whole spine. Methods: A one-year retrospective study was carried out examining PIVD patients who underwent surgical interventions and developed discitis following surgery between 1stSeptember 2022 and 31st August 2023. This research utilized descriptive statisticsto explain each variable under study (including demographics, affected spinal areas, duration of stay for PIVD management, surgical procedures performed, frequency of post-operative discitis, risk factors noted, duration of hospital stay with discitis, and the time interval between discharge and re-admission). At the same time, the Haldane-Anscombe correction is used to illustrate the impact of risk factors on developing post-surgical discitis. Results: Out of the 182 patients who had undergone disc surgeries for diagnosed PIVD, 11 developed post-operative discitis. Disc prolapse and post-opdiscitis both were more frequent in the lumbar spine with a percentage of 48.4 % and 45.5% respectively particularly involving the sacral vertebrae (lumbosacral; 55.5%) compared to other spinal regions. Patients ≥50 age were at greater risk of developing post-op discitis (RR=196.5714). The most common procedure performed for PIVD was Fenestration along with Microdiscectomy, but it was notable that a majority of patients who developed discitis were gone through modified laminectomy plus Microdiscectomy. The hospital stay duration varied considerably, likely reflecting individual patient needs. Conclusion: In the studied population, discitis was found to be rare, affecting only 6.04%. It was more common among older age groups. These findings offer valuable insights into this population’s demographics and surgical trends associated with discitis. Keywords: Discitis, prolapsed disc, PIVD, post-op discitis